Água e multifuncionalidade da agricultura: uma análise a partir dos orizicultores de Cacequi - RS - Soares, Nádia Bolzan (2008)
The multifunctional approach of the agriculture articulates genuinely with the premises institutionalized by the current National Politics of Water Resources, which both result of a logic that looks for to assist to the forts social appeals for the environmental protection and for practices returned to the maintainable development. Before these events, this dissertation approaches as the segment of irrigate rice producers, one of the main users of water resources, they notices the new social demands on the rural, more specifically the environmental. Also it approaches the potential that the adoptions of an economical instrument in the administration of the water tend to influence the users to seek maintainable forms of use of this resource, promoting changes attitudinal in their agricultural practices. The investigation universe was composed by twenty rice producer with farms located in the municipality of Cacequi/RS, which it bases the larger part of its financial income based in the production of irrigated rice. As methodological contribution was used the qualitative approach tends as tools of collection of data through the use of questionnaires and the accomplishment of semi-structured interviews. The study showed that the majority of the rice producers consider the environmental function of the farmer as merely legal obligation. Also it is noticed that, case did not have a rigid legislation and, mainly, if it not intimately harnessed to the monetary logic, it had little change there would be in the posture of these people front to their professional practices that they interfere negatively in the ambient. Although the majority of the irritant rice producers agree that the subject of the water deserves cares, in general, they disagree with the new juridical ordainment that it regulates the use of such a natural resource. The interviewees rice producers evaluate the charge for the reception and use of the water as an instrument merely ornament and without practical efficacy. The great difficulty of this segment of to perceive the agriculture for a logic multifunctional, that it goes besides the production of foods capable to contemplate other functions for the farmer and the agriculture in the contemporary world. The logic that is guiding these rice producers is still of the agriculture as mere cutting of the sectoral economy.